INTEGRASI NILAI KEAGAMAAN DAN KESEHATAN MELALUI PERINGATAN ISRA MI’RAJ UNTUK PENCEGAHAN STUNTING - Rosmi Eni; Muthia Zahra; Najwa Yasmin; Adithiya Hardiansyah; Syaila Nurifki; Yayang Surya Maulana; Karin Sevira Amandra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Stunting is one of the health problems that continues to receive attention in Indonesia because it affects physical growth, cognitive development, and the quality of human resources in the future. This article aims to describe the integration of religious and health values through the commemoration of Isra Mi’raj as an effort to prevent stunting in Nagari Halaban, Lareh Sago Halaban District, Lima Puluh Kota Regency, West Sumatra. The method used in this activity was a qualitative descriptive approach through field observations, documentation, community education, and family assistance. The results of the activity showed that there are still community members experiencing stunting problems due to a lack of understanding regarding nutrition, parenting patterns, and family health. Educational activities conducted through the Isra Mi’raj commemoration had a positive impact on increasing public awareness about the importance of nutritional fulfillment, exclusive breastfeeding, maintaining environmental hygiene, and preventing early marriage. The spiritual approach made health messages easier for the community to accept because they were associated with Islamic teachings and everyday life. This activity demonstrates that the integration of religious and health values can be an effective strategy in increasing public awareness regarding stunting prevention. The synergy between health education, community empowerment, and spiritual approaches is expected to support the creation of a healthy, strong, and high-quality generation.